Life and Living in Protected Areas: An Interpretative Phenomenological Analysis Involving Multiple Stakeholders - George Ștefan Kudor; Dan Florin Stănescu; Marius Constantin Romașcanu (World)
Protected areas (PAs) are essential for conserving biodiversity and supporting sustainable development, particularly in ecologically rich yet administratively challenged regions like Romania. This study aims to understand how key stakeholders—local residents and protected area administrators—experience and interpret conservation management in the Southwestern Carpathians, one of Europe’s last remaining large-scale wilderness areas. Using Interpretative Phenomenological Analysis (IPA), the research offers an in-depth qualitative investigation into how individuals perceive, navigate, and negotiate conservation regulations, socio-economic pressures, and sustainable development goals. The findings highlight a deep emotional connection between residents and nature, juxtaposed with tensions over restrictions, perceived loss of autonomy, and limited compensation. Administrators, in turn, face challenges in enforcing regulations, managing tourism, and engaging communities amidst institutional fragmentation and resource constraints. Key findings emphasize the importance of environmental education, trust-building, and participatory governance in reconciling conservation aims with local development needs. The study underscores the need for inclusive, context-sensitive conservation strategies that integrate community perspectives and facilitate cooperation among local authorities, residents, and administrators. These insights contribute to a deeper understanding of stakeholder dynamics and policy implementation within protected areas, emphasizing the importance of co-produced knowledge and adaptive governance. Future research is encouraged to adopt participatory action approaches and expand stakeholder diversity to support more socially inclusive and ecologically resilient conservation practices.